2003
DOI: 10.1002/joc.887
|View full text |Cite
|
Sign up to set email alerts
|

Cloudiness changes in Cracow in the 20th Century

Abstract: This paper presents the long-term, annual and diurnal cloud amount values for Cracow (Poland) on the basis of 95-year records. Cloud data were taken from climatological observations made at the Department of Climatology, Jagiellonian University, in the years 1906-2000.On the basis of traditional statistical methods, the following values were calculated: average cloudiness (cloud amount), number of cloudless sky occurrences for three climatological terms, daily and yearly averages, and sums of cloudless days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 4 publications
5
26
0
Order By: Relevance
“…Finally, other studies focusing only on one station reported an increase in TCC since the late 19th or the beginning of the 20th centuries: i.e. in Cracow, Poland (Matuszko, 2003;Lewik et al, 2010); in Armagh, Ireland (Pallé and Butler, 2002b); and in Northeastern Spain (Curto et al, 2009). In this latter study, the authors reported a change of around 2 oktas (i.e.…”
Section: A Sanchez-lorenzo Et Al: Increasing Cloud Cover In the 20tmentioning
confidence: 62%
See 1 more Smart Citation
“…Finally, other studies focusing only on one station reported an increase in TCC since the late 19th or the beginning of the 20th centuries: i.e. in Cracow, Poland (Matuszko, 2003;Lewik et al, 2010); in Armagh, Ireland (Pallé and Butler, 2002b); and in Northeastern Spain (Curto et al, 2009). In this latter study, the authors reported a change of around 2 oktas (i.e.…”
Section: A Sanchez-lorenzo Et Al: Increasing Cloud Cover In the 20tmentioning
confidence: 62%
“…Similar trends were confirmed by Croke et al (1999) using a subset of the TCC series for three regions of the US during the 1900-1987 period. Equally, for Canada a systematic increase in TCC was reported between 1901and 1982(McGuffie and Henderson-Sellers, 1988HendersonSellers and McGuffie, 1989;Henderson-Sellers, 1989). The observed trend (about 8 % over the period considered) is slightly lower than for the US, but a sharp increase is also visible in the 1930s-1950s subperiod.…”
Section: A Review Of the Tcc Trends Before The Second Half Of The 20tmentioning
confidence: 80%
“…Changes in the observation period are another source of the lack of data homogeneity (Matuszko, 2003). However, a 1-h difference does not distort a 24-h picture of cloud cover.…”
Section: Data Source and Methodsmentioning
confidence: 99%
“…The St clouds form a full cloud cover. They are among the cloud types with the highest share (13%) of the overall cloudiness in Kraków (Matuszko, 2003) and yield a very low intensity drizzle. During wintertime, in the morning hours, an additional impulse to increase the energy of instability may be provided by the fog that is often encountered in the Vistula valley.…”
Section: Relation Between Diurnal Cycle and Precipitation Typementioning
confidence: 99%